The role of regulation in constituting markets: a co-evolutionary perspective on the UK television production sector. Issue 4 (28th February 2019) - Lourenço, Ana; Turner, Simon
Abstract: This article builds on a legal institutionalist approach to assess market-based regulatory change in British television production over the last three decades. It explores how formal rules governing television production constitute market relations, and whether these rules are likely to be evaded by television producers and commissioners in a context where contracting depends heavily on social norms of cooperation, reciprocity and flexibility. Using qualitative data, this article suggests that changes in law and terms of trade intended to promote a market in television production have not had a straightforward or linear effect: compulsory independent production quotas and licensing models of terms of trade have redrawn organizational boundaries in unexpected ways, disturbed the public service remit and engendered new financial flows. Formal rules were nonetheless central to the trajectory of the television production industry, as they were a constitutive element of changes in the power structure of the sector towards producers' interests.